Metaingatan Dan Hubungannya Dengan Prestasi Ingatan - Hamzah, Mohamad Daud (Penerbit Universiti Sains Malaysia, 1989)
Following a brief review of literature, this paper reveals a theoretical basis to conceptualize metamemory In this conceptualization metamemory is seen as a person's knowledge of memory processes implicated in storage, comprehension and retrieval of information to abstract meanings from item to be remembered